Occipital Lobe Epilepsy With Ictal Fear: Evidence From a Stereo-Electroencephalography (sEEG) Case - Wang, Jing; Wang, Qian; Wang, Mengyang; Luan, Guoming; Zhou, Jian; Guan, Yuguang; Yan, Zhaofen (Frontiers in Neurology, 2018)
Ictal fear is a semiological characters in epilepsy which is a relatively rare phenomenon. Most of the epileptic patients with ictal have epileptic zone in mesial temporal lobe, which is the classical brain area involved in emotion processing. Here we reported a 10-year-old boy suffered with epilepsy with ictal fear as the first manifestation. All the noninvasive evaluation including scalp vEEG, MRI, PET-CT suggested a possible lesion in the left posterior head. The stereo-electroencephalography (sEEG) results showed high frequency direct current shift in left occipital lobe which was ahead of the discharge in amygdala. This case highlights the epileptic network hypothesis which suggested occipital cortex may play an important role in the early emotional network.